A structural and functional model for the tris-histidine motif in cysteine dioxygenase - Anandababu, Karunanithi; Wadepohl, Hubert; Comba, Peter (Chemistry - a European journal, 2019)
The iron(II) complexes [Fe(L)(MeCN)3](SO3CF3)2 (L are two derivatives of tris(2-pyridyl)-based ligands) have been synthesized as models for cysteine dioxygenase (CDO). The molecular structure of one of the complexes exhibits octahedral coordination geometry and the Fe−Npy bond lengths [1.953(4)-1.972(4) Å] are similar to those in the Cys-bound FeII-CDO; Fe−NHis: 1.893-2.199 Å. The iron(II) centers of the model complexes exhibit relatively high FeIII/II redox potentials (E1/2=0.988-1.380 V vs. ferrocene/ferrocenium electrode, Fc/Fc+), within the range for O2 activation and typical for the corresponding nonheme iron enzymes. The reaction of in situ generated [Fe(L)(MeCN)(SPh)]+ with excess O2 in acetonitrile (MeCN) yields selectively the doubly oxygenated phenylsulfinic acid product. Isotopic labeling studies using 18O2 confirm the incorporation of both oxygen atoms of O2 into the product. Kinetic and preliminary DFT studies reveal the involvement of an FeIII peroxido intermediate with a rhombic S= FeIII center (687-696 nm; g≈2.46-2.48, 2.13-2.15, 1.92-1.94), similar to the spectroscopic signature of the low-spin Cys-bound FeIIICDO (650 nm, g≈2.47, 2.29, 1.90). The proposed FeIII peroxido intermediates have been trapped, and the O−O stretching frequencies are in the expected range (approximately 920 and 820 cm−1 for the alkyl- and hydroperoxido species, respectively). The model complexes have a structure similar to that of the enzyme and structural aspects as well as the reactivity are discussed.
Gesehen am 26.11.2019